microRNA-483 ameliorates hypercholesterolemia by inhibiting PCSK9 production - Jianjie Dong; Ming He; Jie Li; Ariane Pessentheiner; Chen Wang; Jin Zhang; Yameng Sun; Wei-Ting Wang; Yuqing Zhang; Junhui Liu; Shen-Chih Wang; Po-Hsun Huang; et al. (JCI Insight, 2020)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) affects cholesterol homeostasis by targeting hepatic LDL receptor (LDLR) for lysosomal degradation. Clinically, PCSK9 inhibitors effectively reduce LDL-cholesterol (LDL-C) levels and the incidence of cardiovascular events. Because microRNAs (miRs) are integral regulators of cholesterol homeostasis, we investigated the involvement of miR-483 in regulating LDL-C metabolism. Using in silico analysis, we predicted that miR-483-5p targets the 3′-UTR of PCSK9 mRNA. In HepG2 cells, miR-483-5p targeted the PCSK9 3′-UTR, leading to decreased PCSK9 protein and mRNA expression, increased LDLR expression, and enhanced LDL-C uptake. In hyperlipidemic mice and humans, serum levels of total cholesterol and LDL-C were inversely correlated with miR-483-5p levels. In mice, hepatic miR-483 overexpression increased LDLR levels by targeting Pcsk9, with a significant reduction in plasma total cholesterol and LDL-C levels. Mechanistically, the cholesterol-lowering effect of miR-483-5p was significant in mice receiving AAV8 PCSK9-3′-UTR but not Ldlr-knockout mice or mice receiving AAV8 PCSK9-3′-UTR (ΔBS) with the miR-483-5p targeting site deleted. Thus, exogenously administered miR-483 or similarly optimized compounds have potential to ameliorate hypercholesterolemia.